Protective Effects of Geniposide and Genipin against Hepatic Ischemia/Reperfusion Injury in Mice - Kim, Joonki; Kim, Hyo-Yeon; Lee, Sun-Mee (KOREAN SOC APPLIED PHARMACOLOGY, 2013)
Geniposide is an active product extracted from the gardenia fruit, and is one of the most widely used herbal preparations for liver disorders. This study examined the cytoprotective properties of geniposide and its metabolite, genipin, against hepatic ischemia/reperfusion (I/R) injury. C57BL/6 mice were subjected to 60 min of ischemia followed by 6 h of reperfusion. Geniposide (100 mg/kg) and genipin (50 mg/kg) were administered orally 30 min before ischemia. In the I/R mice, the levels of serum alanine aminotransferase and hepatic lipid peroxidation were elevated, whereas hepatic glutathione/glutathione disulfide ratio was decreased. These changes were attenuated by geniposide and genipin administration. On the other hand, increased hepatic heme oxygenase-1 protein expression was potentiated by geniposide and genipin administration. The increased levels of tBid, cytochrome c protein expression and caspase-3 activity were attenuated by geniposide and genipin. Increased apoptotic cells in the I/R mice were also significantly reduced by geniposide and genipin treatment. Our results suggest that geniposide and genipin offer significant hepatoprotection against I/R injury by reducing oxidative stress and apoptosis.
Keywords: LIVER-CELL INJURY; GARDENIA-JASMINOIDES; ISCHEMIA-REPERFUSION; HEME OXYGENASE-1; PC12 CELLS; RAT-LIVER; APOPTOSIS; EXPRESSION; PATHWAY; DAMAGE